Internet Usage and its Addiction among School-going Adolescents in an Urban District of India - Ginni Agrawal; Piyush Jain; Ramesh Verma (Preventive Medicine: Research & Reviews, 2024)
Introduction: Internet addiction is inability to control the use of internet, leading to physical, psychological or social difficulties. Materials and Methods: A school based study was conducted among adolescents of urban Rohtak, Haryana, using a pre-tested, semi-structured questionnaire and Young’s Internet Addiction test. Results: Out of 600 participants, 44.17% were female. This study showed widespread internet use among adolescents (86%). The main purpose of internet use was entertainment (95%). The estimated prevalence of internet addiction was high (66.86%). Internet addiction was higher among males (P = 0.001). Conclusion: There is a need to counsel children regarding the appropriate use of internet and balancing the time between internet surfing, studies and outdoor physical activities.